Collectivism Impairs Team Performance When Relational Goals Conflict With Group Goals - Qin, Xin; Chi Yam, Kai; Ye, Wenping; Zhang, Junsheng; Liang, Xueji; Zhang, Xiaoyu; Savani, Krishna (Personality & social psychology bulletin, 2024)
This research challenges the idea that teams from more collectivistic cultures tend to perform better. We propose that in contexts in which there are tradeoffs between group goals (i.e., what is best for the group) and relational goals (i.e., what is best for one’s relationships with specific group members), people in less collectivistic cultures primarily focus on group goals but those in more collectivistic cultures focus on both group and relational goals, which can lead to suboptimal decisions. An archival analysis of 100 years of data across three major competitive team sports found that teams from more collectivistic nations consistently underperformed, even after controlling for a number of nation and team characteristics. Three follow-up studies with 108 Chinese soccer players, 109 Singapore students, and 119 Chinese and the U.S. adults provided evidence for the underlying mechanism (i.e., prioritizing relational goals over group goals). Overall, this research suggests a more balanced view of collectivism, highlighting an important context in which collectivism can impair team performance.